Prevalence of drugs of abuse found in testing of illicit drug seizures and urinalysis of selected population in Hong Kong. (June 2019) - Cheng, Wing-Chi; Dao, Kwok-Leung
Graphical abstract: Highlights: Ketamine, MA and heroin were the top three prevalent abused drugs in 2011–2015. Increase in popularity of MA use but usage of ketamine was decreasing. Positive rates of urinalysis were steady (1 in 5) where single drug use predominant. 47 NPS identified with synthetic/plant based cathinones (˜77%) mostly encountered. Abstract: The study investigates the prevalence of drugs of abuse detected from 2011 to 2015 through (i) forensic drug testing of illicit drug seizures from law enforcement agencies; and (ii) analysis of common drugs of abuse in urine samples obtained from offenders/probationers under mandatory drug-use surveillance programmes. Under the selected drug testing groups, there were an average of 5334 cases/year of illicit drug seizures examined and 28, 438 samples/year requiring drugs of abuse analysis in urine, from 2011 to 2015. The drug positive rates for urinalysis in the selected population group (i.e., offenders/probationers requiring mandatory drug testing) were steady with an average of about 22%. The ratio of single drug use to more than one drug was about 4:1, showing predominant use of single drug. Ketamine, methamphetamine (MA) and heroin were the three most commonly encountered abused drugs through laboratory testing. During the period, identification of ketamine was shown to decline continuously in both illicit drug testing and urinalysis while there was substantial increase in detection of MA. A rising trend was noted for cases identified with new psychotropic substances (NPS) in illicit drug seizures although NPS cases contributed to a small proportion of overall drug seizure cases examined (<5%) in the study period. A total of 47 substances classified as NPS were encountered with cathinones, either synthetic or plant-based, contributed to the majority of NPS cases (˜77%) followed by synthetic cannabinoids and phenethylamines.